Agronomic performance, variance component, and diversity of sixty-two sweet potato accessions - WIWIT RAHAJENG; S. A. RAHAYUNINGSIH (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Rahajeng W, Rahayuningsih SA. 2017. Agronomic performance, variance component, and diversity of sixty-two sweet potato accessions. Biodiversitas 18: 95-100. Sweet potato is an alternative carbohydrate source to overcome the shortage of rice due to the impact of the global change. The objectives of this research were to determine the performance, the genotypic and phenotypic variance, and the diversity of agronomic characters of sixty-two germplasm accessions of sweet potato. The research was conducted in April-August 2013 at Muneng Research Station, Probolinggo, East Java, Indonesia. The material used was sixty-two accessions of sweet potato from Indonesian Legumes and Tuber Crops Research Institute (ILETRI) germplasm collection. The research was arranged in a randomized complete block design (RCBD) with two replications with a plot size of 1 m Ã— 5 m and 100 Ã— 25 cm in spacing (single row). The variables observed included: the vines length, the branch number, the chlorophyll index, the weight of the canopy, the harvest index, the storage root length, the storage root diameter, the number of the storage root per plot, the storage root yield, and dry matter content. The analysis of variance showed the high significant genotype at all the traits observed. All the traits showed a wide range of phenotypic variance and genotypic variance and high broad sense heritability. The PCA identified four principal components that explained 79.00% of total variation present in the genotypes. The traits that most contributed to the diversity were the chlorophyll index, the weight of vines, the vines length, and the branch number. The cluster analysis based on 69% similarity grouped sixty-two accessions into ten clusters, genotypes with superior traits currently on the first cluster. MLG 12695 and MLG 12505 were potentially used as a source of genes in the superior sweet potato varieties improved for the high yield potential purpose. Keywords: agronomic characters, diversity, Ipomoea batatas, sweet potato, variance